WORKSHOP RADIOLOGI TATA LAKSANA PEMERIKSAAN HSG PADA KASUS INFERTILITAS SERTA SOSIALISASI PENGISIAN SIPORLIN DAN MANAJEMEN ORGANISASI - Aulia Annisa; Danil Hulmansyah; Shelly Angella; Indrapuri, R. Sri Ayu (LPPM Universitas Awal Bros, 2023)
The PARI Pengda Riau organization as one of the health professions in Riau Province, never stops trying to improve the professional skills of Radiographers through Workshop or Seminar activities, both local, regional, national and international. This activity is very important so that Radiographers in Riau Province can find out various information about technological developments in the field of Radiology and applicable laws so that they can work with high professionalism and responsibility. For this reason, we intend to hold community service in the form of a local workshop in collaboration with radiology professional organizations with the title